2009
DOI: 10.1111/j.1365-2982.2009.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of enteric nerve functions in the inflamed and postinflamed gut

Abstract: Inflammation of the gut alters the properties of the intrinsic and extrinsic neurons that innervate it. While the mechanisms of neuroplasticity differ amongst the inflammatory models that have been used, amongst various regions of the gut, and between intrinsic versus extrinsic neurons, a number of consistent features have been observed. For example, intrinsic and extrinsic primary afferent neurons become hyperexcitable in response to inflammation, and interneuronal synaptic transmission is facilitated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 73 publications
(182 reference statements)
0
63
1
1
Order By: Relevance
“…Gastrointestinal inXammation is known to be associated with enteric neuroplasticity and changes in neurochemistry, the mechanisms of which may diVer amongst the inXammatory models that have been used. In other words, it has been shown that responses of the ENS to inXammation may vary according to the site and type of inXammation based on the inXammatory stimulus (Giaroni et al 1999;Lomax et al 2005;Mawe et al 2009;Vasina et al 2006). Therefore, in our study dealing with the eVect of inXammation on the expression of MrgE and MrgF, two distinct models of intestinal inXammation were used, to allow for the identiWcation of possible model speciWc eVects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gastrointestinal inXammation is known to be associated with enteric neuroplasticity and changes in neurochemistry, the mechanisms of which may diVer amongst the inXammatory models that have been used. In other words, it has been shown that responses of the ENS to inXammation may vary according to the site and type of inXammation based on the inXammatory stimulus (Giaroni et al 1999;Lomax et al 2005;Mawe et al 2009;Vasina et al 2006). Therefore, in our study dealing with the eVect of inXammation on the expression of MrgE and MrgF, two distinct models of intestinal inXammation were used, to allow for the identiWcation of possible model speciWc eVects.…”
Section: Discussionmentioning
confidence: 98%
“…These data led us to speculate that MrgE and MrgF are expressed in the enteric nervous system (ENS), since enteric neurons are known to be a source of sensory innervation in the GI tract enabling the decentralized gut to perform complex reXex functions (Blackshaw et al 2007). Further, changes in MrgE and MrgF expression can be expected in intestinal inXammatory conditions as a consequence of the plasticity of the ENS and the sensitization of sensory pathways during intestinal inXammation (Bielefeldt et al 2009;Giaroni et al 1999;Lomax et al 2005;Mawe et al 2009;Vasina et al 2006), and such changes may vary depending on the nature of the inXammatory stimulus. However, to date, no detailed expression data on MrgE and MrgF are available in the gut in normal or inXamed circumstances.…”
Section: Introductionmentioning
confidence: 98%
“…GI smooth muscle activities are coordinated by enteric nerves that innervate the muscle. Emerging evidence indicated that inflammation or infection can alter GI functions through immune mediators that interact with and influence the neurophysiological, neurochemical, and morphological properties of enteric nerves (20). IL-33 induced a hypercontractile response to EFS and increased spontaneous contractions that were retained partially in both STAT6…”
Section: Discussionmentioning
confidence: 99%
“…Usually, during intestinal inflammation there is a decrease in the numbers of submucosal and myenteric neurons and changes to enteric glial cells within the enteric ganglia. These acute changes in neuronal cell numbers are accompanied by changes in specific neuronal activity, including the integrated motor and secretory functions of the intestine [44]. GLP-2 in this state is able to enhance survival of the enteric neurons in culture and to counteract mast cell induced neuronal cell death [45].…”
Section: Glp-2 In the Ens During Inflammationmentioning
confidence: 99%